Efforts to Improve Basic Underhand Passing Skills in Volleyball Using Digital Technology and Playing Methods for Grade VIII Students of SMP Negeri 35 Palembang - Wicaksono, Prabowo Aji; Hartati, Hartati; Yusaromi, M. Armando (Jurnal Pendidikan Jasmani (JPJ), 2024)
This study aims to determine the improvement of volleyball underhand passing learning outcomes with digital technology and playing methods in class VIII.6 students of SMP Negeri 35 Palembang. The type of this research is PTK (classroom action research). The subjects of this study were 31 students. The research instrument used was the assessment of volleyball underhand passing skills. From the results of the research and data analysis, this study can improve efforts to improve volleyball underhand passing skills using digital technology and playing methods of class VIII 6 students of SMP Negeri 35 Palembang. With the percentage of classical completeness in cycle I of 21 students or 67.7%, while in cycle II it became 27 students or 87.7%.